2021
DOI: 10.1371/journal.pone.0260609
|View full text |Cite
|
Sign up to set email alerts
|

Object detection for automatic cancer cell counting in zebrafish xenografts

Abstract: Cell counting is a frequent task in medical research studies. However, it is often performed manually; thus, it is time-consuming and prone to human error. Even so, cell counting automation can be challenging to achieve, especially when dealing with crowded scenes and overlapping cells, assuming different shapes and sizes. In this paper, we introduce a deep learning-based cell detection and quantification methodology to automate the cell counting process in the zebrafish xenograft cancer model, an innovative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…At last, we evaluate SAT on object detection and identify images of bicycle and electric bicycle. According to our training protocol, SAT model appears perfect performance, such as mAP (Albuquerque et al,2021) and maxDets (Shermin et al,2021). The Average Precision (AP) reaches 95%, the small area metric reaches 90%, the medium area metric reaches 94.8% and the large area metric reaches 94.5%, as shown in Table 4.…”
Section: Object Detectionmentioning
confidence: 84%
“…At last, we evaluate SAT on object detection and identify images of bicycle and electric bicycle. According to our training protocol, SAT model appears perfect performance, such as mAP (Albuquerque et al,2021) and maxDets (Shermin et al,2021). The Average Precision (AP) reaches 95%, the small area metric reaches 90%, the medium area metric reaches 94.8% and the large area metric reaches 94.5%, as shown in Table 4.…”
Section: Object Detectionmentioning
confidence: 84%
“…Upon comparing with the existing literature, we found that our development was empirically performing better, in terms of mAP and accuracy. Similar models were deployed for cancer cell counting and detection in zebrafish xenografts 29 . The study mentioned that the entirely fine-tuned model was able to achieve an mAP of 0.8457, considering all the background noise in the images and avoiding all the unwanted small artifacts in the images.…”
Section: Discussionmentioning
confidence: 99%
“…A DL-based cell classification and counting system were created using the inception (ResNet V2) feature extractor, a highly tuned architecture based on the FR-CNN. Compared to conventional Faster R-CNN, their technique increased the average precision of the tested data set from 71% to 85% ( Albuquerque et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%